The c1 repressor of bacteriophage P1 operator-repressor interaction of wild-type and mutant repressor proteins. - Heinrich, J (1989)
The c1 repressor gene of bacteriophage P1 and the temperature-sensitive mutants P1c1.100 and P1c1.162 was cloned into an expression vector and the repressor proteins were overproduced. A rapid purification procedure was required for the isolation of the thermolabile repressor proteins. Identification of the highly purified protein of an apparent molecular weight of 33,000 as the product of the c1 gene was verified by (i) the coincidence of partial amino acid sequences determined experimentally to that deduced from the c1 DNA sequence, and (ii) the temperature-sensitive binding to the operator DNA of the thermolabile repressor proteins. Analysis of the products of c1-c1.100 recombinant DNAs relates the thermolability to an unknown alteration in the C-terminal half of the c1.100 repressor. Binding to the operator DNA of c1 repressor is sensitive to N-ethylmaleimide. Since the only three cysteine residues are located in the C-terminal half of the repressor it is suggested that this part of the molecule is important for the binding to the operator DNA. This assumption is supported by the findings that a 14-kDa C-terminal repressor fragment obtained by cyanogen bromide cleavage retains DNA binding properties.